Osborne Ccna 640-801 Study Guide - Deal, Richard (McGraw-Hill, 2011)
The Most Complete CCNA Software Exam Preparation Package Available! This study guide provides 100% complete coverage of all objectives for the newly revised CCNA exam, and also covers exam objectives for the INTRO and ICND exams. The book includes an interactive CD containing powerful network simulation tools and exam preparation software powered by Boson Software. The CD contains more than 20 Labs from the book and features hundreds of commands, more than Four Hundred practice exam questions and answers with full explanations, and more than Eight hours of CertCam video training on how to perform complex configurations with IOS commands. All of the step-by-step exercises from the book function with the simulator and give you critical hands-on experience along with the end-of-chapter lab questions that challenge you to think critically and apply knowledge from the chapters. The CD also includes Flash cards for PC, Pocket PC, or Palm (Three hundred original questions and answers), and a free Subnet Calculator and Configuration Register.